Role of α5β1 and αvβ3 Integrins on Smooth Muscle Cell Spreading and Migration in Fibrin Gels - Ikari, Yuji; Yee, Karen O.; Schwartz, Stephen M. (Thrombosis and Haemostasis, 2000)
Fibrin is found at sites of vascular injury and is one of the major matrix ligands for β3 integrins. Blocking the β3 integrin on smooth muscle cell is hypothesized as a potential target to prevent restenosis because it could inhibit cell attachment and migration into fibrin provisional matrix. Human aortic smooth muscle cells (HNB18E6E7) spread stably in plasma gels within 24 h. Cell spreading was dramatically blocked by simultaneous use of α5β1 and αvβ3 integrin antibodies (P <0.0001), however, blocking of either integrin alone failed to inhibit spreading. GPenGRGDSPCA, which has been considered a specific αvβ3 antagonist, inhibited spreading at 500 µM, suggesting that the peptide blocked both α5β1 and αvβ3. Similarly, invasive migration into fibrin gels was blocked by simultaneous use of both α5β1 and αvβ3 antibodies, however, blocking of either integrin alone failed to effect cell migration. Another migration assay using transwell indicated similar results. In conclusion, both α5β1 and αvβ3 integrins are responsible for smooth muscle cell spreading and migration into fibrin gels. These data suggest that blocking β3 integrin alone would not affect smooth muscle cell interaction with fibrin.
Keywords: Fibrinogen; RGD peptide; fibrin gel contraction